Axillary Bud Proliferation Approach for Plant Biodiversity Conservation and Restoration. (6th April 2014) - Ngezahayo, F.; Liu, B.
Abstract : Due to mainly human population pressure and activities, global biodiversity is getting reduced and particularly plant biodiversity is becoming at high risk of extinction. Consequently, many efforts have been deployed to develop conservation methods. Because it does not involve cell dedifferentiation of differentiated cells but rather the development and growth of new shoots from preexisting meristems, the axillary bud proliferation approach is the method offering least risk of genetic instability. Indeed, meristems are more resistant to genetic changes than disorganized tissues. The present review explored through the scientific literature the axillary bud proliferation approach and the possible somaclonal variation that could arise from it. Almost genetic stability or low level of genetic variation is often reported. On the contrary, in a few cases studied to date, DNA methylation alterations often appeared in the progenies, showing epigenetic variations in the regenerated plants from axillary bud culture. Fortunately, epigenetic changes are often temporary and plants may revert to the normal phenotype. Thus, in the absence of genetic variations and the existence of reverting epigenetic changes over time, axillary bud culture can be adopted as an alternative nonconventional way of conserving and restoring of plant biodiversity.